FKASA-Civer Dragon- Champion of Netball, FSKKP-Arctic Fox- Champion of Futsal UMP Super 5 - Siti Nurfarmy, Ibrahim (2019)
FKASA-Civer Dragon emerged as the champion for Universiti Malaysia Pahang (UMP) Netball League with FKKSA-Humble Bee taking the second spot and FKM-Mecha Rhino at third place.